Language and utilisation of emergency care in Queensland. (29th November 2012) - Mahmoud, Ibrahim; Hou, Xiang‐Yu; Chu, Kevin; Clark, Michele
Abstract Objective To compare access and utilisation of EDs in Queensland public hospitals between people who speak only English at home and those who speak another language at home. Methods A retrospective analysis of a Queensland statewide hospital ED dataset (ED Information System) from 1 January 2008 to 31 December 2010 was conducted. Access to ED care was measured by the proportion of the state's population attending EDs. Logistic regression analyses were performed to determine the relationships between ambulance use and language, and between hospital admission and language, both after adjusting for age, sex and triage category. Results The ED utilisation rate was highest in English only speakers (290 per 1000 population), followed by Arabic speakers (105), and lowest among German speakers (30). Compared with English speakers, there were lower rates of ambulance use in Chinese (odds ratio 0.50, 95% confidence interval, 0.47–0.54), Vietnamese (0.87, 0.79–0.95), Arabic (0.87, 0.78–0.97), Spanish (0.56, 0.50–0.62), Italian (0.88, 0.80–0.96), Hindi (0.61, 0.53–0.70) and German (0.87, 0.79–0.90) speakers. Compared with English speakers, German speakers had higher admission rates (odds ratio 1.17, 95% confidence interval, 1.02–1.34), whereas there were lower admission rates in Chinese (0.90, 0.86–0.99), Arabic (0.76, 0.67–0.85) and Spanish (0.83, 0.75–0.93) speakers. Conclusion This study showed that there was a significant association between lower utilisation of emergency care and speaking languages other than English at home. Further researches are needed using in‐depth methodology to investigate if there are language barriers in accessing emergency care in Queensland.